Performance of hydrogen generation system with acid accelerated hydrolysis of solid-state sodium borohydride - Kim, Do Hoon; Koh, Jae Seon; Lee, Sehyeok; Jaewon, Kirk; Jeong, Hyang soo; Kim, Yongmin; Kim, Min Soo (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
This research explores the formic acid-enhanced hydrolysis of solid-state sodium borohydride (SBH) in aqueous environments as a method for generating hydrogen suitable for high-power fuel cell applications. Conducted at moderate temperatures (60-90 degrees C), the reactions effectively suppress the formation of carbon monoxide, a known contaminant for fuel cell catalysts. The study systematically investigates how variations in acid feed concentration, reactant temperature, and the quantity of formic acid influence reaction kinetics and product distribution. To further elucidate the chemical dynamics, solid-state 11B NMR spectroscopy was employed to characterize the resulting boron-containing residues. Across all tested conditions, both the injection rate of the acid and the operating temperature were found to significantly impact the rate of hydrogen evolution. Notably, higher temperatures compensated for reduced acid quantities, enabling consistently high conversion efficiencies and reinforcing the temperature-dependent nature of SBH hydrolysis.